PROPOSAL OF AN ASSESSMENT TO CHARACTERIZE WORLDVIEWS AND LEVELS OF CONSCIOUSNESS IN ORGANIZATIONS - Gabardo, Luciana; Stacheski, Marianne Ales; Cordeiro, José Vicente Bandeira de Mello (Caderno PAIC, 2022)
Assessments of worldviews and levels of consciousness are essentials in organizational interventions guided by an integral approach. Consultants and leaders might have a much easier task on promoting change if they can infer the levels of consciousness that are activated in a certain situation. Nevertheless, most of the assessments currently available present difficulties to effectively identify the process of thinking or the stage of consciousness one is really operating from. Most of them that can be filled within less than half an hour ended up focusing on exposed values, not on how people actually think. Other assessments that indeed grasp the thinking processes are based on hour-long in-person interviews. This work aimed to develop a new assessment capable of identifying respondents’ level of consciousness without demanding very qualified interviewers and a long-time process, seeking its internal validation. The final version of the assessment presents two different sections. The first section contains thirty objective questions focusing on five different situations, using a seven-point Likert scale for each question, in order to reduce bias. The second section comprises eighteen subjective sentence completion questions (SCT). The internal validation was performed for the thirty objective questions, presenting a high coefficient on Cronbach’s Alpha scale (0,8138), considered an excellent score. The analysis of the SCT answers were made manually. Its results were very consistent with the objective questions and enabled the proper identification of deep internalized values and thinking processes, but will require further automation with the help of a Content Analysis Software.